2019
DOI: 10.1021/acscatal.9b01772
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Liquid Modification on the ORR Performance and Degradation Mechanism of Trimetallic PtNiMo/C Catalysts

Abstract: Ionic liquids (ILs) modification, following the concept of “solid catalyst with ionic liquid layer (SCILL)”, has been demonstrated to be an effective approach to improving both activity and stability of Pt-based catalysts for the oxygen reduction reaction. In this work, the SCILL concept has been applied to a trimetallic PtNiMo/C system, which has been documented recently to be significantly advantageous over the benchmark PtNi-based catalysts for oxygen reduction. To achieve this, two hydrophobic ILs ([BMIM][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(118 citation statements)
references
References 58 publications
4
114
0
Order By: Relevance
“…Comparing the CVs of Pt/ C and Pt/Pd/C with/without IL, the H adsorption peaks for the ILmodified system were slightly suppressed, and the peaks shifted to a lower potential range, which agreed with previous reports. 25,37 These results suggest that the presence of IL suppresses the access of H on the Pt surface by reducing the bonding strength of Pt and H through a ligand effect [37][38][39] and/or the occupation of certain Pt sites by IL molecules. 38 leads to slow ORR kinetics.…”
Section: Electrochemical Measurementsmentioning
confidence: 89%
See 2 more Smart Citations
“…Comparing the CVs of Pt/ C and Pt/Pd/C with/without IL, the H adsorption peaks for the ILmodified system were slightly suppressed, and the peaks shifted to a lower potential range, which agreed with previous reports. 25,37 These results suggest that the presence of IL suppresses the access of H on the Pt surface by reducing the bonding strength of Pt and H through a ligand effect [37][38][39] and/or the occupation of certain Pt sites by IL molecules. 38 leads to slow ORR kinetics.…”
Section: Electrochemical Measurementsmentioning
confidence: 89%
“…21,22 A hydrophobic ionic liquid (IL) modification of Pt surface has recently emerged as another method to enhance the activity of Pt-based catalysts for ORR. [23][24][25] Many groups have investigated the ability of IL modifications to enhance ORR activity with a variety of IL. [26][27][28] Snyder et al firstly reported the development of a new architecture in which high surface area and nanoporous Ni-Pt alloy nanoparticles encapsulated with a hydrophobic [7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD)][bis(pentafluoroethylsulfonyl)imide (BETI)] IL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, synthetic procedures have been introduced that allow for controlled and smaller loading of ILs. They consist of the dilution of the catalyst and the desired amount of IL in isopropanol, [ 13,29,31,13–13 ] ethanol, [ 12 ] or ethanol/water mixtures, [ 33 ] generally followed by mixing, sonication, and evaporation. Du and coworkers utilized 10 min sonication, followed by 3 h of magnetic stirring, partial solvent evaporation by vacuum desiccation, and centrifugation to isolate the catalyst.…”
Section: Solid Catalysts With An Il Layermentioning
confidence: 99%
“…From top to bottom presented data were originally reported as follows: Pt/C, [ 29 ] Pt/C, [ 35 ] Pt/C, [ 31 ] Pt/C, [ 72 ] np‐NiPt, [ 30 ] np‐NiPt, [ 28 ] np‐NiPt/C, [ 73 ] PtNiMo/C. [ 36 ] Detailed information about the experimental parameters are presented in Table S2, Supporting Information. b) Oxygen reduction current, obtained by IL‐modified PGM‐free catalysts.…”
Section: Solid Catalysts With An Il Layermentioning
confidence: 99%